Effects of proprioception and resistance band training on joint kinesthesia and injury prevention in elite gymnasts - Murgia, C. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: Positive effects of strength and proprioceptive training in ankle and knee rehabilitation protocols of injured athletes are well documented in the literature. The results of this research have provided an impetus for early introduction of strength and proprioception conditioning into rehabilitation protocols. The purpose of this study was to examine the effects of proprioception and resistance band conditioning on inferior extremity joint kinesthesia and initial injury occurrence in gymnasts. Methods Female elite gymnasts (N=92), aged 13 to 21, were randomly selected from nationally recognized gymnastics centers. Subjects trained 30-35 hours per week. An injury survey was administered; ankle and knee goniometric measurements and joint position sense were recorded before and after treatment period. Subjects were randomly assigned to the following treatment groups: (1) combination (resistance band and rehabilitation/dance proprioception), (2) resistance band, (3) proprioception, and (4) controls. Gymnasts engaged in conditioning regimens 3 times per week for 10 weeks, beginning four weeks prior to and during the early part of the competitive season. A one-way repeated measures ANOVA was used. Scheffe' post hoc tests and correlation were used to analyze differences and examine relationships when significance was found.